Direct Channel or Distribution Channel? The Role of Internet-Based Targeted Advertising With Vertical Differentiation in Distinct Channels - Zhao Jiang; Wu Dan; Zhou Huini (SAGE Open)
The selection of optimal channels is considered the critical marketing strategy for the firm. Effective vertical channel selection could induce distinct effects on the firm’s profit and social warfare by selecting a specific type of advertising. Otherwise, as the targeted population is quite different for the firm using mass or targeted advertising, this differentiation is becoming more significant for the population in the final marketing channel. Within the vertical differentiation model, the role of Internet-based targeted advertising on direct sales and distribution channels is studied. Compared to mass advertising, the firm using Internet-based targeted advertising in distinct channels can benefit the firm’s equilibrium profit by reducing advertising waste and enhancing the product’s price. The manufacturer might use Internet-based targeted advertising to control the total profit of the channel. Meanwhile, Internet-based targeted advertising might reduce the retailer’s and the entire channel’s profit. Otherwise, the targeting accuracy of the firm shows a bidirectional role in the firm’s equilibrium price in the direct channel. The firm’s equilibrium advertising level and profit might be reduced with the increasing targeting accuracy. The public department of the government needs to consider the potential risk of targeted advertising that might reduce the real benefits of distribution channels and harm the development of the market.